Systematics and improvement of classification of resource base of the bank - Вовчак, Ольга Дмитрівна; Алілуйко, Марія Степанівна (Technology audit and production reserves, 2015)
The article analyzes and summarizes the main approaches to classification of constituents of resource base of banks and taking into account that it is proposed the generalized (integrated) classification of the resource base of commercial banks. Particular attention is paid to the specific types of components of the resource base of the bank. It is grounded limited interpretation of the term structure of the resource base in the economic literature and formulated its own definition as the ratio between the individual items of equity and bank liabilities (raised and borrowed funds) and between different elements of the resource base of the bank as a whole in order to ensure stability and reducing investment of raised and borrowed resources. Based on existing approaches to classification of structural elements of the resource base of the bank, it is developed their classification by the most essential features that can solve the strategic objectives of the bank on sourcing resource base with minimal cost to implement active operations in certain directions and volumes and aimed at efficient use and management of the resource base. It is introduced an additional criterion for classification of bank resources for their functionality, whereby they are three components: resources to formation of portfolio of earning assets; resources to create material, technical and technological base of the bank; resources to self-insurance of bank from banking risks.